2022
DOI: 10.1038/s41598-022-10393-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential cannabidiol (CBD) repurposing as antibacterial and promising therapy of CBD plus polymyxin B (PB) against PB-resistant gram-negative bacilli

Abstract: This study aimed to assess the ultrapure cannabidiol (CBD) antibacterial activity and to investigate the antibacterial activity of the combination CBD + polymyxin B (PB) against Gram-negative (GN) bacteria, including PB-resistant Gram-negative bacilli (GNB). We used the standard broth microdilution method, checkerboard assay, and time-kill assay. CBD exhibited antibacterial activity against Gram-positive bacteria, lipooligosaccharide (LOS)-expressing GN diplococcus (GND) (Neisseria gonorrhoeae, Neisseria menin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The non-psychotropic phytocannabinoid cannabidiol (CBD) was found to be highly potent against Gram-positive bacteria through disruption of the bacterial membrane [803][804][805]. Interestingly, the combined treatment of CBD with polymyxin B showed a synergistic effect against some Gram-negative bacteria including Acinetobacter baumannii, Klebsiella pneumoniae, and Escherichia coli [804,806,807].…”
Section: Antibiotic Adjuvantsmentioning
confidence: 99%
“…The non-psychotropic phytocannabinoid cannabidiol (CBD) was found to be highly potent against Gram-positive bacteria through disruption of the bacterial membrane [803][804][805]. Interestingly, the combined treatment of CBD with polymyxin B showed a synergistic effect against some Gram-negative bacteria including Acinetobacter baumannii, Klebsiella pneumoniae, and Escherichia coli [804,806,807].…”
Section: Antibiotic Adjuvantsmentioning
confidence: 99%
“…In addition to the data presented in Table 1 , Table 2 and Table 3 , acid-fast bacteria have also been considered while there are multiple other recent studies that report anti-microbial activities associated with CIMPS, but where MICs were not presented. The minimum inhibitory concentrations of CBD for Mycobacterium tuberculosis H37Rv ATCC 27294 and M. tuberculosis CF86 have been reported as 12.5 and 25 mg/mL, respectively [ 31 ]. Zheljazkov et al have reported that essential oils from Cannabis sativa L. cv.…”
Section: The Antimicrobial Properties Of Cannabis and Cannabis-derive...mentioning
confidence: 99%
“…The use of cannabinoids as antimicrobial adjuncts, rather than as standalone therapeutics, has also been considered. For example, the combination of polymyxin B and CBG is efficient at killing E. coli [ 12 ], and CBD seems to enhance the efficacy of polymyxin B against multiple strains of A. baumanni , K. pneumoniae and P. aeruginosa [ 31 , 97 ]. The independent and combined efficacy of CBD and bacitracin against S. aureus and L. monocytogenes is presented in Figure 1 , as extracted from Wassman et al [ 41 ].…”
Section: Translational Considerations For the Development Of Cannabis...mentioning
confidence: 99%
“…The lack of antibiotic development in the 21 st century has enhanced the need for researchers to repurpose antibiotics and determine treatment methods that help retain their antibacterial function. The use of agents extracted from botanical sources as synergetic additives has been an area of growing interest over recent history [15,37,39,40]. This study explored the potential synergistic activity between C. sativa L. CBD extract and three broad spectrum antibiotics: ampicillin, kanamycin, and polymyxin-B.…”
Section: Comparative Kinetics Of Antibiotic-cbd Co-treatmentmentioning
confidence: 99%
“…Recent studies have observed CBD's antibacterial activity against several clinically relevant pathogens including Staphylococcus aureus, Streptococcus pneumoniae, Clostridium difficile, Neisseria spp., Moraxella catarrhalis, Legionella pneumophila, and Salmonella spp. [13][14][15][16][17]. With the increased prevalence and occurrence of antimicrobial resistance posing a significant threat to public health, the development of novel antibacterial agents is a necessity [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%